2016
DOI: 10.7567/jjap.55.04er11
|View full text |Cite
|
Sign up to set email alerts
|

Threshold-voltage instability in 4H-SiC MOSFETs with nitrided gate oxide revealed by non-relaxation method

Abstract: Threshold voltage (V th ) shift of 4H-SiC metal-oxide-semiconductor field effect transistors with N 2 O post-oxidation annealing (POA) was measured by sweep and non-relaxation methods. Although the V th shift values for both the samples were almost identical when measured by the sweep method, those for the Ar POA samples were larger than those for the N 2 O POA samples when measured by the non-relaxation method. Thus, it is difficult to investigate the exact V th shifts by using only the conventional sweep met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…To overcome this problem, by referring to the BTI measurements without V T relaxation of state-of-theart Si MOS devices, 330,331) the non-relaxation method was applied to various SiC MOSFETs and an accurate evaluation of the fast V T shift under the various stressing conditions has recently been made. 243,332,333) This advanced non-relaxation method detected extremely large V T shifts in…”
Section: Reliability Of Sic Mos Devicesmentioning
confidence: 99%
“…To overcome this problem, by referring to the BTI measurements without V T relaxation of state-of-theart Si MOS devices, 330,331) the non-relaxation method was applied to various SiC MOSFETs and an accurate evaluation of the fast V T shift under the various stressing conditions has recently been made. 243,332,333) This advanced non-relaxation method detected extremely large V T shifts in…”
Section: Reliability Of Sic Mos Devicesmentioning
confidence: 99%
“…[3][4][5] The traps located near the interface are considered to be responsible for the fast relaxation of the threshold voltage (V th ) shift in SiC MOSFETs. 6) Therefore, investigation of NITs is very important. The NITs on SiC have been evaluated; [7][8][9][10][11] however, the spatial distribution of NITs is not considered in conventional analysis methods, and the nature of NITs remains under debate.…”
mentioning
confidence: 99%
“…32) In addition, the significant NIT density decrease with increasing nitridation time is consistent with the results reported by Sometani et al, in which fast V th shift values were reduced by nitridation, compared with those of dry samples. 6) In conclusion, the NITs in SiO 2 =4H-SiC MOS structures were investigated using a distributed circuit model. It was found that this model can be applied to SiC MOS capacitors, but we must assume an exponential NIT distribution to explain the frequency dependence of both the capacitance and conductance in the strong-accumulation condition.…”
mentioning
confidence: 99%
“…Such a relatively long interval is not recommended in terms of precise evaluation of the instability of V th [36]. Due to the long interval, the amount of charges with a fast detrapping time constant cannot be evaluated by our measurement procedure [35]. In other words, obtained results in this study show the effect of charges with a slow time constant on the radiation response of MOSFETs.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, remarkable increase of σ p J p was not observed and the annealing effect was not extracted from the fitting results. These suggest that most of the hole traps are located close to the SiC/SiO 2 interface [35]. Due to the suppression of movement of holes toward the interface by negatively large E ox , a portion of holes generated by irradiation could be trapped.…”
Section: Discussionmentioning
confidence: 99%